Targeted regulatory T cell activation by site-specific PEGylated interleukin-2 mitigates autoimmune inflammation - Masahiro Ikeda; Shinpei Yamaguchi; Shigeki Takaoka; Yasuko Sakaguchi; Shunki Yasui (Journal of Translational Autoimmunity)
Dysregulation of immune homeostasis accompanied by regulatory T cell (Treg) dysfunction is a hallmark of various autoimmune and inflammatory diseases. While low-dose interleukin-2 (IL-2) treatment can enhance Treg levels and alleviate disease symptoms, its short half-life necessitates frequent dosing. Furthermore, adverse events associated with the activation of other immune cells are often observed. In this study, using a site-specific PEGylation approach, we developed a novel IL-2 variant, I129-W80, which exhibited an IL-2Rα–biased binding profile, driven by the steric hindrance of the PEG moiety. It selectively activated Tregs in vitro and could overcome inhibition by the endogenous decoy receptor, soluble IL-2Rα, unlike the Fc-fusion IL-2 variant AMG-592. In a single-dose monkey study, I129-W80 demonstrated an extended half-life, along with sustained amplification and activation of Tregs. At the maximum dose that did not induce C-reactive protein elevation, I129-W80 showed superior activity compared with AMG-592. I129-W80 improved inflammatory responses in both delayed-type hypersensitivity and xenogeneic graft-versus-host disease models. Additionally, in an imiquimod-induced dermatitis model, I129-W80 exhibited reduced distribution to inflamed tissues compared with AMG-592. These findings demonstrated that I129-W80 possesses distinct properties relative to Fc-fusion IL-2 variant and can correct immune imbalances caused by Treg dysfunction, thereby improving the symptoms of various autoimmune diseases.